HTLV-1-associated infective dermatitis and probable HTLV-1- associated myelopathy in an adolescent female - Raquel Bisacotti Steglich; Renata Elise Tonoli; Paulo Ricardo Martins Souza; Giselle Martins Pinto; Rudimar dos Santos Riesgo (Sociedade Brasileira de Dermatologia, 2015)
AbstractHuman T cell lymphotropic virus type 1 (HTLV-1)-associated infective dermatitis (ID) is a chronic, severe and recurrent eczema occurring during childhood in patients vertically infected with HTLV-1. HTLV-1-associated myelopathy/tropical spastic paraparesia (HAM/ TSP) is slow and progressive. We report the case of an adolescent female from a non-endemic area for HTLV-1 who presents ID and, most likely, associated HAM/TSP.